Nasopharyngeal sarcoidosis: a clinical case - Kseniia I. Sapova; Stanislav S. Gaydukov; Aleksey V. Voronov; Arkadiy N. Naumenko; Irina I. Sarkisyan (ZAO "Consilium Medicum", 2022)
Sarcoidosis is a chronic multisystem inflammatory disease characterized by non-caseous granulomas, most commonly in the lungs and intrathoracic lymph nodes. The nasopharyngeal disease is a rare localization of sarcoidosis. Clinical presentations include difficulty in nasal breathing, rhinophonia, and postnasal syndrome. Nasopharyngeal endoscopy, computed tomography, and magnetic resonance imaging are the main diagnostic methods for detecting lesions in this area. The histological examination provides the diagnosis verification. Considering the frequent secondary spread of sarcoidosis, all patients should consult a rheumatologist to select adequate systemic therapy. We provide a clinical case illustrating the management of a patient with nasopharyngeal sarcoidosis.